Prozesssicherheit von Laserschneidmaschinen Auflagemessung und Schachtelung - Struckmeier, Frederick (Forschungsberichte aus der Industriellen Informationstechnik, 2022)
The aim of this work is the design and validation of an image-based optimization of laser flatbed cutting machines to avoid tilted parts. Three different approaches for the visual detection of the slats are presented and, based on this, it is discussed to what extent a change in the nesting of the parts to be produced can be used to increase efficiency.